PsycEXTRA Dataset 2005
DOI: 10.1037/e609712011-003
|View full text |Cite
|
Sign up to set email alerts
|

From Kindergarten Through Third Grade: Children's Beginning School Experiences

Abstract: (NCES) fulfills a congressional mandate to collect and report "statistics and information showing the condition and progress of education in the United States and other nations in order to promote and accelerate the improvement of American education." EDUCATION STATISTICS QUARTERLY Purpose and goals At NCES, we are convinced that good data lead to good decisions about education. The Education Statistics Quarterly is part of an overall effort to make reliable data more accessible. Goals include providing a quic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
96
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 9 publications
6
96
0
Order By: Relevance
“…Overall problem behavior scores were low; however, children with lower achievement and more family risk factors tended to rate themselves higher on both of the problem behavior scales. 18 These findings, although they are disturbing, are not surprising to pediatricians, who have long been advocates for underserved pediatric populations. This inequity in school readiness, which is apparent at school entry and is associated with persistent academic underachievement and social-emotional risk, points to a need to address these differences before children enter kindergarten, especially for families and children at risk.…”
Section: How Ready Are Us Children As They Enter Kindergarten?mentioning
confidence: 96%
“…Overall problem behavior scores were low; however, children with lower achievement and more family risk factors tended to rate themselves higher on both of the problem behavior scales. 18 These findings, although they are disturbing, are not surprising to pediatricians, who have long been advocates for underserved pediatric populations. This inequity in school readiness, which is apparent at school entry and is associated with persistent academic underachievement and social-emotional risk, points to a need to address these differences before children enter kindergarten, especially for families and children at risk.…”
Section: How Ready Are Us Children As They Enter Kindergarten?mentioning
confidence: 96%
“…Walston and West (2004) found evidence of positive effects of full-day attendance on math and reading score gains over the kindergarten year. Rathbun and West (2004) found that these positive full-day kindergarten effects did not sustain into third grade.…”
mentioning
confidence: 89%
“…As noted, Rathbun et al (2004) reported sex differences in math achievement among first graders using the Early Childhood Longitudinal Program-Kindergarten Cohort (ECLS-K) data set.…”
Section: Specific Cognitive Tasksmentioning
confidence: 99%